Power of Automotive Supplier Cluster: The Case of BMW in South Carolina - Selcuk Karayel (European Scientific Journal, ESJ, 2017)
The phenomenon of regional industrial concentration, or agglomerations, has been studied for more than a century. Over the past couple of decades, interest has dramatically doubled both from the aspects of academics and policy makers. However, the process of making a car requires more sophisticated and complex technology and an upper level of knowledge. The collaboration is indeed an inevitable tool. The agglomeration of the automotive industry in the upper Midwest of the US is one of the most prominent and persistent industrial clusters. Historically, automotive production in the US was dominated by the big three domestic manufacturers, namely: Ford, GM, and Chrysler. However, in the last 30 years, many foreign-owned manufacturers (e.g. Honda, BMW) have opened assembly lines in the South which is far away from the automotive industry center in Michigan (Rosenbaum, 2013). These assemblers were attracted to the South due to the lower rates of unionization and lower labor costs in those states. In this paper, the researcher focus on the competitiveness of this collaboration, if there is any, by using three star analysis and the strength of foreign trade capabilities by Vollrath Analysis.